Shifting Society in Response to the Tourism Industry: A Case Study of New Challenges in Lombok Utara - Hasan Basri; Mohamad Tamrin; Dani Alfatwari (Sekolah Vokasi, Universitas Gadjah Mada, 2020)
This paper examines shifts in society in response to tourism development in Lombok Utara. This research scientifically demonstrates the emergence of new problems due to the economic and ecological impact of tourism and the breakdown of tradition. Fishbone analysis was used to map a variety of issues from trusted sources through direct observation and in-depth interviews. Findings show that a gap exists between expected and actual economic advantages as farmers and fishermen transition to tourism. The skill deficit and competitiveness brought about only a minor effect on the prosperity of host communities, even if a large economic incentive was generated by the government from taxes. The ecological damage resulting from human activity (abrasion, rubbish, energy consumption, coral reef destruction) will be detrimental for future generations. Traditions of the host communities are also threatened.